2007
DOI: 10.1111/j.1365-2044.2007.05259.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimum and optimum light requirements for laryngoscopy in paediatric anaesthesia: a manikin study*

Abstract: Summary Direct laryngoscopy is performed regularly in paediatric anaesthetic practice for the purpose of intubating a patient's trachea. A minimum illumination of 700 lux at a distance of 20 mm has been suggested in a draft standard for laryngoscopes from the International Organization for Standardization. We investigated the minimum and optimum illumination required by anaesthetists during laryngoscopy. Fifty anaesthetists were recruited to perform laryngoscopy on a child manikin with a selection of laryngosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…Of note, although our indoor MIC appeared to be higher than the MIC of Scholz et al 13 and Malan et al 14 MIC, these authors held their laryngoscope tip 20 mm above their light sensor, while we held our tip 10 mm above our light sensor. We chose the 10-mm distance as this configuration allowed the laryngoscope light source to be approximately the same distance from the light sensor as the laryngoscope light source would be from the patient's vocal cords during laryngoscopy.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Of note, although our indoor MIC appeared to be higher than the MIC of Scholz et al 13 and Malan et al 14 MIC, these authors held their laryngoscope tip 20 mm above their light sensor, while we held our tip 10 mm above our light sensor. We chose the 10-mm distance as this configuration allowed the laryngoscope light source to be approximately the same distance from the light sensor as the laryngoscope light source would be from the patient's vocal cords during laryngoscopy.…”
Section: Discussioncontrasting
confidence: 59%
“…More recent studies have found that the minimal laryngoscope illumination may even be lower than that required by the international standard. 13,14 In one study, 13 anesthetists intubating manikins found that the MIC ranged from a median of 9-34 lux, depending on the bulb used, and in another manikin study, 14 anesthetists found that the median MIC was between 1 and 7 lux. Similarly, in our study, the mean MIC at our indoor setting, designed to simulate the illumination in an operating room, was 92.5 lux, significantly lower than the MIC of 867 lux in the study by Skilton et al All laryngoscopes from our previous study 5 would have met this 92.5-lux MIC.…”
Section: Discussionmentioning
confidence: 99%
“…In a manikin study involving 50 anesthetists, the majority of participants considered 700 lux laryngoscope illuminance to be too bright. These anesthetists indicated that they could tolerate relatively low levels of illumination for simple laryngoscopy, but suggested that a brighter light would be desirable for a difficult intubation with highest optimum level of 610 lux and lowest optimum of 16 lux reported (7). It should be emphasized that these subjective assessments were conducted on a child manikin and did not assess performance during a difficult clinical laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have sought to identify optimum illuminance and luminance (2)(3)(4)(5)(6)(7)(8); however, a variety of methods, endpoints, and results have made comparison difficult. The International Organization for Standardization (ISO) has now established a standard for laryngoscope light (1).…”
Section: Organization For Standardization (Iso) 7376:2009mentioning
confidence: 99%
“…These data were recorded in two ways, both from the fully off position up to the optimum level and from the maximum brightness down to the optimum level. 4 The order of the testing scenario was block randomized. After testing was complete, the participants were asked which bulb colour they preferred.…”
mentioning
confidence: 99%